Characterization of recombinant human cytomegaloviruses encoding IE1 mutants L174P and 1-382 reveals that viral targeting of PML bodies perturbs both intrinsic and innate immune responses - Scherer, Myriam; Otto, Victoria; Stump, Joachim; Klingl, Stefan; Müller, Regina; Reuter, Nina; Muller, Yves; Sticht, Heinrich; Stamminger, Thomas (Journal of Virology, 2015)
PML is the organizer of cellular structures termed nuclear domain 10 (ND10) or PML-nuclear bodies (PML-NBs) that act as key mediators of intrinsic immunity against human cytomegalovirus (HCMV) and other viruses. The antiviral function of ND10 is antagonized by viral regulatory proteins such as the immediate early protein IE1 of HCMV. IE1 interacts with PML through its globular core domain (IE1) and induces ND10 disruption in order to initiate lytic HCMV infection. Here, we investigate the consequences of a point mutation (L174P) in IE1CORE, which was shown to abrogate the interaction with PML, for lytic HCMV infection. We found that a recombinant HCMV encoding IE1-L174P displays a severe growth defect similar to that of an IE1 deletion virus. Bioinformatic modeling based on the crystal structure of IE1 suggested that insertion of proline into the highly alpha-helical domain severely affects its structural integrity. Consistently, L174P mutation abrogates the functionality of IE1 and results in degradation of the IE1 protein during infection. In addition, our data provide evidence that IE1 as expressed by a recombinant HCMV encoding IE1 1-382 not only is required to antagonize PML-mediated intrinsic immunity but also affects a recently described function of PML in innate immune signaling. We demonstrate a coregulatory role of PML in type I and type II interferon-induced gene expression and provide evidence that upregulation of interferon-induced genes is inhibited by IE1. In conclusion, our data suggest that targeting PML by viral regulatory proteins represents a strategy to antagonize both intrinsic and innate immune mechanisms.
EVALuna2:8299

Contribution of the Major ND10 Proteins PML, hDaxx and Sp100 to the Regulation of Human Cytomegalovirus Latency and Lytic Replication in the Monocytic Cell Line THP-1 - Wagenknecht, Nadine; Reuter, Nina; Scherer, Myriam; Reichel, Anna; Müller, Regina; Stamminger, Thomas (Viruses, 2015)
Promyelocytic leukemia nuclear bodies, also termed nuclear domain 10 (ND10), have emerged as nuclear protein accumulations mediating an intrinsic cellular defense against viral infections via chromatin-based mechanisms, however, their contribution to the control of herpesviral latency is still controversial. In this study, we utilized the monocytic cell line THP-1 as an in vitro latency model for human cytomegalovirus infection (HCMV). Characterization of THP-1 cells by immunofluorescence andWestern blot analysis confirmed the expression of all major ND10 components. THP-1 cells with a stable, individual knockdown of PML, hDaxx or Sp100 were generated. Importantly, depletion of the major ND10 proteins did not prevent the terminal cellular differentiation of THP-1 monocytes. After construction of a recombinant, endotheliotropic human cytomegalovirus expressing IE2-EYFP, we investigated whether the depletion of ND10 proteins affects the onset of viral IE gene expression. While after infection of differentiated, THP-1-derived macrophages as well as during differentiation-induced reactivation from latency an increase in the number of IE-expressing cells was readily detectable in the absence of the major ND10 proteins, no effect was observed in non-differentiated monocytes. We conclude that PML, hDaxx and Sp100 primarily act as cellular restriction factors during lytic HCMV replication and during the dynamic process of reactivation but do not serve as key determinants for the establishment of HCMV latency.
EVALuna2:8283

Controlled crystal dehydration triggers a space-group switch and shapes the tertiary structure of cytomegalovirus immediate-early 1 (IE1) protein - Klingl, Stefan; Scherer, Myriam; Stamminger, Thomas; Muller, Yves (Acta Crystallographica Section D: Biological Crystallography, 2015)
Cytomegalovirus immediate-early 1 (IE1) protein is a key viral effector protein that reprograms host cells. Controlled dehydration experiments with IE1 crystals not only extended their diffraction limit from 2.85 to 2.3Å resolution but also triggered a monoclinic to tetragonal space-group transition with only minor alterations in the unit-cell parameters. An analysis of the pre-dehydration and post-dehydration crystal structures shows how dehydration rearranges the packing of IE1 molecules to meet the unit-cell constraints of the higher lattice symmetry. The transition from P21 to P43 reduces the number of copies in the asymmetric unit from four to two, and molecules previously related by noncrystallographic symmetry merge into identical crystallographic copies in the tetragonal space group. At the same time, dehydration considerably alters the tertiary structure of one of the two remaining IE1 chains in the asymmetric unit. It appears that this conformational switch is required to compensate for a transition that is assumed to be unfavourable, namely from a highly preferred to a rarely observed space group. At the same time, the dehydration-triggered molecular reshaping could reveal an inherent molecular flexibility that possibly informs on the biological function of IE1, namely on its binding to target proteins from the host cell.
Keywords: free-mounting system; humidity-control device; improved scattering and diffraction; lattice symmetry increase; space-group transition; viral effector protein

Crystal structure of cytomegalovirus IE1 protein reveals targeting of TRIM family member PML via coiled-coil interactions - Scherer, Myriam; Klingl, Stefan; Sevvana, Madhumati; Otto, Victoria; Schilling, Eva-Maria; Stump, Joachim; Müller, Regina; Reuter, Nina; Sticht, Heinrich; Muller, Yves; Stamminger, Thomas (PLoS Pathogens, 2014)
PML nuclear bodies (PML-NBs) are enigmatic structures of the cell nucleus that act as key mediators of intrinsic immunity against viral pathogens. PML itself is a member of the E3-ligase TRIM family of proteins that regulates a variety of innate immune signaling pathways. Consequently, viruses have evolved effector proteins to modify PML-NBs; however, little is known concerning structure-function relationships of viral antagonists. The herpesvirus human cytomegalovirus (HCMV) expresses the abundant immediate-early protein IE1 that colocalizes with PML-NBs and induces their dispersal, which correlates with the antagonization of NB-mediated intrinsic immunity. Here, we delineate the molecular basis for this antagonization by presenting the first crystal structure for the evolutionary conserved primate cytomegalovirus IE1 proteins. We show that IE1 consists of a globular core (IE1CORE) flanked by intrinsically disordered regions. The 2.3 Å crystal structure of IE1CORE displays an all ?-helical, femur-shaped fold, which lacks overall fold similarity with known protein structures, but shares secondary structure features recently observed in the coiled-coil domain of TRIM proteins. Yeast two-hybrid and coimmunoprecipitation experiments demonstrate that IE1CORE binds efficiently to the TRIM family member PML, and is able to induce PML deSUMOylation. Intriguingly, this results in the release of NB-associated proteins into the nucleoplasm, but not of PML itself. Importantly, we show that PML deSUMOylation by IE1CORE is sufficient to antagonize PML-NB-instituted intrinsic immunity. Moreover, co-immunoprecipitation experiments demonstrate that IE1CORE binds via the coiled-coil domain to PML and also interacts with TRIM5? We propose that IE1CORE sequesters PML and possibly other TRIM family members via structural mimicry using an extended binding surface formed by the coiled-coil region. This mode of interaction might render the antagonizing activity less susceptible to mutational escape.
EVALuna2:8238

Emerging Role of PML Nuclear Bodies in Innate Immune Signaling - Scherer, Myriam; Stamminger, Thomas (Journal of Virology, 2016)
Research in the last 2 decades has demonstrated that a specific organelle of the cell nucleus, termed PML nuclear body (PML-NB) or nuclear domain 10 (ND10), is frequently modified during viral infection. This correlates with antagonization of a direct repressive function of individual PML-NB components, such as the PML, hDaxx, Sp100, or ATRX protein, that are able to act as cellular restriction factors. Recent studies now reveal an emerging role of PML-NBs as coregulatory structures of both type I and type II interferon responses. This emphasizes that targeting of PML-NBs by viral regulatory proteins has evolved as a strategy to compromise intrinsic antiviral defense and innate immune responses.
EVALuna2:8322

Human Cytomegalovirus Particles Treated with Specific Antibodies Induce Intrinsic and Adaptive but Not Innate Immune Responses - Wu, Zeguang; Qin, Ruifang; Wang, Li; Bosso, Matteo; Scherer, Myriam; Stamminger, Thomas; Hotter, Dominik; Mertens, Thomas; Frascaroli, Giada (Journal of Virology, 2017)
Human cytomegalovirus (HCMV) persistently infects 40% to 100% of the human population worldwide. Experimental and clinical evidence indicates that humoral immunity to HCMV plays an important role in restricting virus dissemination and protecting the infected host from disease. Specific immunoglobulin preparations from pooled plasma of adults selected for high titers of HCMV antibodies have been used for the prevention of CMV disease in transplant recipients and pregnant women. Even though incubation of HCMV particles with these preparations leads to the neutralization of viral infectivity, it is still unclear whether the antibody-treated HCMV particles (referred to here as HCMV-Ab) enter the cells and modulate antiviral immune responses. Here we demonstrate that HCMV-Ab did enter macrophages. HCMV-Ab did not initiate the expression of immediate early antigens (IEAs) in macrophages, but they induced an antiviral state and rendered the cells less susceptible to HCMV infection upon challenge. Resistance to HCMV infection seemed to be due to the activation of intrinsic restriction factors and was independent of interferons. In contrast to actively infected cells, autologous NK cells did not degranulate against HCMV-Ab-treated macrophages, suggesting that these cells may not be eliminated by innate effector cells. Interestingly, HCMV-Ab-treated macrophages stimulated the proliferation of autologous adaptive CD4+and CD8+T cells. Our findings not only expand the current knowledge on virus-antibody immunity but may also be relevant for future vaccination strategies.IMPORTANCEHuman cytomegalovirus (HCMV), a common herpesvirus, establishes benign but persistent infections in immunocompetent hosts. However, in subjects with an immature or dysfunctional immune system, HCMV is a major cause of morbidity and mortality. Passive immunization has been used in different clinical settings with variable clinical results. Intravenous hyperimmune globulin preparations (IVIg) are obtained from pooled adult human plasma selected for high anti-CMV antibody titers. While HCMV neutralization can be shownin vitrousing different systems, data are lacking regarding the cross-influence of IVIg administration on the cellular immune responses. The aim of this study was to evaluate the effects of IVIg on distinct components of the immune response against HCMV, including antigen presentation by macrophages, degranulation of innate natural killer cells, and proliferation of adaptive CD4+and CD8+T cells.
EVALuna2:33751

Human promyelocytic leukemia protein is targeted to distinct subnuclear domains in plant nuclei and colocalizes with nucleolar constituents in a SUMO-dependent manner - Lamm, Christian; Scherer, Myriam; Reuter, Nina; Amin, Bushra; Stamminger, Thomas; Sonnewald, Uwe (FEBS Open Bio, 2016)
Eukaryotic nuclei are subdivided into subnuclear structures. Among the most prominent of these structures are the nucleolus and the PML nuclear bodies (PML-NBs). PML-NBs are spherical multiprotein aggregates of varying size localized in the interchromosomal area. PML-NB formation is dependent on the presence of the promyelocytic leukemia protein (PML) as well as on post-translational modification of core components by covalent attachment of the small ubiquitin-like modifier (SUMO). So far, PML-NBs as well as PML have been described in mammalian cells only, whereas no orthologs are known in the plant kingdom. In order to investigate conserved mechanisms in PML targeting, we expressed human PML (hPML) fused to the GFP in Nicotiana benthamiana. Using confocal laser scanning microscopy and coimmunoprecipitation followed by mass spectrometric analysis, we found the fusion protein in association with nucleolar constituents. Importantly, mutants of hPML, which are no longer SUMOylated, showed altered localizations, implying SUMO-dependent targeting of hPML in plants as has previously been shown for mammalian cells. Interestingly, in the presence of proteasome inhibitors, hPML could also be found in the nucleolus of mammalian cells suggesting conserved targeting mechanisms of PML across kingdoms. Finally, Solanum tuberosum COP1, a proposed PML-like protein from plants, was fused to the red fluorescent protein (RFP) and coexpressed with hPML::eGFP. Microscopic analysis confirmed the localization of COP1::RFP in nuclear speckles. However, hPML::eGFP did not colocalize with COP1::RFP. Hence, we conclude that plants do not possess specialized PML-NBs, but that their functions may be covered by other subnuclear structures like the nucleolus.
Keywords: nucleolus; plant subnuclear structures; promyelocytic leukemia protein; nuclear bodies; small ubiquitin like modifier

Small ubiquitin-related modifier (SUMO) pathway-mediated enhancement of human cytomegalovirus replication correlates with a recruitment of SUMO-1/3 proteins to viral replication compartments - Scherer, Myriam; Reuter, Nina; Wagenknecht, Nadine; Otto, Victoria; Sticht, Heinrich; Stamminger, Thomas (Journal of General Virology, 2013)
Recent studies have suggested that the small ubiquitin-related modifier (SUMO) conjugation pathway may play an important role in intrinsic antiviral resistance and thus for repression of herpesviral infections. In particular, it was shown that the herpes simplex virus type-1 regulatory protein ICP0 acts as a SUMO-targeted ubiquitin ligase (STUbL), inducing the widespread degradation of SUMO-conjugated proteins during infection. As the IE1 protein of human cytomegalovirus (HCMV) is known to mediate a de-SUMOylation of PML, we investigated whether HCMV uses a similar mechanism to counteract intrinsic antiviral resistance. We generated primary human fibroblasts stably expressing FLAG-SUMO-1 or FLAG-SUMO-3 and analysed the SUMOylation pattern after HCMV infection or isolated IE1 expression. However, Western blot experiments did not reveal a global loss of SUMO conjugates, either in HCMV-infected or in IE1-expressing cells, arguing against a function of IE1 as an STUbL. Interestingly, we observed that FLAG-SUMO-1 and FLAG-SUMO-3, subsequent to IE1-mediated promyelocytic leukemia protein (PML) de-SUMOylation and the consequent disruption of PML nuclear bodies, were recruited into viral replication compartments. This raised the question of whether FLAG-SUMO-1/3 might promote HCMV replication. Intriguingly, overexpression of FLAG-SUMO-1/3 enhanced accumulation of viral DNA, which correlated with an increase in viral replication and in virus particle release. Together, these data indicate that HCMV, in contrast to other herpesviruses, has evolved subtle mechanisms enabling it to utilize the SUMO conjugation pathway for its own benefit, resulting in an overall positive effect of SUMO conjugation for HCMV replication.
EVALuna2:8191

The Human CMV IE1 Protein: An Offender of PML Nuclear Bodies - Scherer, Myriam; Schilling, Eva-Maria; Stamminger, Thomas (Advances in Anatomy Embryology and Cell Biology, 2017)
PML nuclear bodies (PML-NBs) are SUMOylation-dependent, highly complex protein assemblies that accumulate in the interchromosomal territories of the cell nucleus. Research of the last two decades revealed that many viruses have evolved effector proteins that modify PML-NBs. This correlates with antagonization of individual PML-NB components which act as host cell restriction factors. The multifunctional immediate-early protein IE1 of human cytomegalovirus directly interacts with the PML protein resulting in a disruption of the dot-like structure of PML-NBs. This review summarizes recent advances on the functional consequences of PML-NB modification by IE1. In particular, we describe that PML exerts a novel co-regulatory role during the interferon response which is abrogated by IE1. Via binding to PML, IE1 is able to compromise both intrinsic antiviral defense mechanisms and classical innate immune responses. These interactions of IE1 with innate host defenses are crucial for the onset of lytic replication and, consequently, may represent promising targets for antiviral strategies.
EVALuna2:35297

The human cytomegalovirus IE1 protein antagonizes PML nuclear body-mediated intrinsic immunity via the inhibition of PML de novo SUMOylation - Schilling, Eva-Maria; Scherer, Myriam; Reuter, Nina; Schweininger, Johannes; Muller, Yves; Stamminger, Thomas (Journal of Virology, 2017)
PML nuclear bodies (NBs) are accumulations of cellular proteins embedded in a scaffold-like structure built by SUMO-modified PML/TRIM19. PML and other NB proteins act as cellular restriction factors against human cytomegalovirus (HCMV); however, this intrinsic defense is counteracted by the immediate early protein 1 (IE1) of HCMV. IE1 directly interacts with the PML coiled-coil domain via its globular core region and disrupts NB foci by inducing a loss of PML SUMOylation. Here, we demonstrate that IE1 acts via abrogating the de novo SUMOylation of PML. In order to overcome reversible SUMOylation dynamics, we made use of a cell-based assay that combines inducible IE1 expression with a SUMO mutant resistant to SUMO proteases. Interestingly, we observed that IE1 expression did not affect preSUMOylated PML; however, it clearly prevented de novo SUMO conjugation. Consistent results were obtained by in vitro SUMOylation assays, demonstrating that IE1 alone is sufficient for this effect. Furthermore, IE1 acts in a selective manner, since K160 was identified as the main target lysine. This is strengthened by the fact that IE1 also prevents AsO-mediated hyperSUMOylation of K160, thereby blocking PML degradation. Since IE1 did not interfere with coiled-coil-mediated PML dimerization, we propose that IE1 affects PML autoSUMOylation either by directly abrogating PML E3 ligase function or by preventing access to SUMO sites. Thus, our data suggest a novel mechanism for how a viral protein counteracts a cellular restriction factor by selectively preventing the de novo SUMOylation at specific lysine residues without affecting global protein SUMOylation.
EVALuna2:33771
Keywords: Human cytomegalovirus; Immediate early 1; Intrinsic immunity; Nuclear domain 10; PML nuclear bodies; Sumoylation

The Major Immediate-Early Protein IE2 of Human Cytomegalovirus Is Sufficient to Induce Proteasomal Degradation of CD83 on Mature Dendritic Cells - Heilingloh, Christiane; Grosche, Linda; Kummer, Mirko; Mühl-Zürbes, Petra; Kamm, Lisa; Scherer, Myriam; Latzko, Melanie; Stamminger, Thomas; Steinkasserer, Alexander (Frontiers in Microbiology, 2017)
Human cytomegalovirus (HCMV) is the prototypic beta-herpesvirus and widespread throughout the human population. While infection is asymptomatic in healthy individuals, it can lead to high morbidity and mortality in immunocompromised persons. Importantly, HCMV evolved multiple strategies to interfere with immune cell function in order to establish latency in infected individuals. As mature DCs (mDCs) are antigen-presenting cells able to activate naïve T cells they play a crucial role during induction of effective antiviral immune responses. Interestingly, earlier studies demonstrated that the functionally important mDC surface molecule CD83 is down-regulated upon HCMV infection resulting in a reduced T cell stimulatory capacity of the infected cells. However, the viral effector protein and the precise mechanism of HCMV-mediated CD83 reduction remain to be discovered. Using flow cytometric analyses, we observed significant down-modulation of CD83 surface expression becoming significant already 12 h after HCMV infection. Moreover, Western bot analyses revealed that, in sharp contrast to previous studies, loss of CD83 is not restricted to the membrane-bound molecule, but also occurs intracellularly. Furthermore, inhibition of the proteasome almost completely restored CD83 surface expression during HCMV infection. Results of infection kinetics and cycloheximide-actinomycin D-chase experiments, strongly suggested that an HCMV immediate early gene product is responsible for the induction of CD83 down-modulation. Consequently, we were able to identify the major immediate early protein IE2 as the viral effector protein that induces proteasomal CD83 degradation.
EVALuna2:26039

The ND10 Component Promyelocytic Leukemia Protein Acts as an E3 Ligase for SUMOylation of the Major Immediate Early Protein IE1 of Human Cytomegalovirus - Reuter, Nina; Schilling, Eva-Maria; Scherer, Myriam; Müller, Regina; Stamminger, Thomas (Journal of Virology, 2017)
Previous studies identified the nuclear domain 10 (ND10) components promyelocytic leukemia protein (PML), hDaxx, and Sp100 as factors of an intrinsic immune response against human cytomegalovirus (HCMV). This antiviral function of ND10, however, is antagonized by viral effector proteins like IE1p72, which induces dispersal of ND10. Furthermore, we have shown that both major immediate early proteins of HCMV, IE1p72 and IE2p86, transiently colocalize with ND10 subnuclear structures and undergo modification by the covalent attachment of SUMO. Since recent reports indicate that PML acts as a SUMO E3 ligase, we asked whether the SUMOylation of IE1p72 and IE2p86 is regulated by PML. To address this, PML-depleted fibroblasts, as well as cells overexpressing individual PML isoforms, were infected with HCMV. Western blot experiments revealed a clear correlation between the degree of IE1p72 SUMO conjugation and the abundance of PML. On the other hand, the SUMOylation of IE2p86 was not affected by PML. By performingin vitroSUMOylation assays, we were able to provide direct evidence that IE1p72 is a substrate for PML-mediated SUMOylation. Interestingly, disruption of the RING finger domain of PML, which is proposed to confer SUMO E3 ligase activity, abolished PML-induced SUMOylation of IE1p72. In contrast, IE1p72 was still efficiently SUMO modified by a SUMOylation-defective PML mutant, indicating that intact ND10 bodies are not necessary for this effect. Thus, this is the first report that the E3 ligase PML is capable of stimulating the SUMOylation of a viral protein which is supposed to serve as a cellular mechanism to compromise specific functions of IE1p72.IMPORTANCEThe major immediate early proteins of human cytomegalovirus, termed IE1p72 and IE2p86, have previously been shown to undergo posttranslational modification by covalent coupling to SUMO moieties at specific lysine residues. However, the enzymatic activities that are responsible for this modification have not been identified. Here, we demonstrate that the PML protein, which mediates an intrinsic immune response against HCMV, specifically serves as an E3 ligase for SUMO modification of IE1p72. Since SUMO modification of IE1p72 has previously been shown to interfere with STAT factor binding, thus compromising the interferon-antagonistic function of this viral effector protein, our finding highlights an additional mechanism through which PML is able to restrict viral infections.
EVALuna2:33764